The Palacio de Oquendo, an elite residence in the lower valley of the Chillón river - Allcca Aiquipa, Noelia (2021)
This research work is the study of the importance and functionality of the Palacio de Oquendo archaeological site, based on the architectural study. It will focus on the study and analysis of the architectural components present in the archaeological site Palacio de Oquendo, as in the site and architectural design you are presenting. In this sense, it is relevant to note that, throughout the literature included for this site, a variety of works from the Palacio Oquendo site can be found roughly studied, within investigations in the Lower Valley of Chillón, in archaeological sites located in Oquendo and not focusing on Palacio de Oquendo, especially on the role it would have fulfilled in the Middle Horizon. Therefore, the present work aims to contribute to the knowledge about the function that the Oquendo Palace played and characterize the site as an elite residence, which we are postulating.